PENERAPAN TEKNIK KAMERA HANDHELD UNTUK MENINGKATKAN UNSUR DRAMATIK DALAM FILM PENDEK UNPAID SOULS - Diputra, Komang Purna; Payuyasa, I Nyoman; Pandet, Putu Raditya (CALACCITRA: JURNAL FILM DAN TELEVISI, 2025)
Unpaid Souls is a thriller short film that emphasizes a dramatic and suspenseful atmosphere. The story follows a group of gamblers struggling to survive in a game of death. The shooting not only focuses on angles and lighting, but also uses handheld techniques to give the impression of flexibility and free movement following the storyline. This technique creates an intimate and emotional atmosphere, making the audience feel the moment more deeply. This study aims to explore the effectiveness of using handheld in building emotional atmosphere and character connection with the audience. The results show that handheld emphasizes emotional instability and strengthens the audience's immersion, especially in conflict scenes or emotional moments.